ANALISIS KESALAHAN STRUKTUR KALIMAT DALAM MENULIS MAHASISWA PBSI UNIKA WIDYA MANDALA MADIUN - Mudjiyono, Gregorius (Widya Warta, 2017)
This study aims to describe the type of sentence structure errors in writing theses and editing the standard Indonesian language conducted by students of Study Program of Indonesian Language and Literature Education, Faculty of Teacher Training and Education, Catholic University of Widya Mandala Madiun. This study made use of descriptive qualitative design. The data of the research are sentence errors obtained from two sources, namely students’ theses and the results of the practice of editing language errors. The data were collected using the technique of note-taking and classification. The data analysis was done applying distributional method with the technique of immediate constituent analysis, deletion, insertion, and read-marker technique. The results of the data analysis showed that the type of sentence structure errors found is as follows (1) ambiguity between subject function and modifier function, (2) ambiguity between sentence introduction and predicate function, (3) ambiguity between compound sentence and complex sentence, and (4) ambiguity between independent clause and dependent clause.